An Empirical Enquiry into Stakeholders’ Perception of Electricity Pricing Methodology - Kyari, Adam Konto; Lawal, Labaran Mohammed (International Journal of Energy Economics and Policy, 2021)
This study investigates stakeholders’ perception of the sustainability of Nigeria’s MYTO pricing methodology vis-Ã -vis government’s electricity efficiency objectives. Using a five-point Likert questionnaire, data was collected and analysed via descriptive and regression analyses. The results indicate that 96% of the variations in electricity pricing is accounted for by government’s electricity efficiency objectives of acceptability, accessibility and availability. The study concludes that Nigeria’s MYTO pricing regime is sustainable. Similarly, the study concludes that there is policy inadequacy in addressing fundamental issues of end users’ lack of awareness of pricing system and mistrust between industry players. Although these conclusions have met the objectives of the study, the study recommends further research on the impact of subsidy on sustainability of electricity pricing methodology. Keywords; electricity, pricing, sustainability JEL Classifications: E3, L94, P18 DOI: https://doi.org/10.32479/ijeep.10534